Pemanfaatan Sampah Kertas HVS, Serbuk Kayu Sengon (Paraserianthes falcataria) dan Kulit Singkong (Manihot utilissima) sebagai Bahan Pembuatan Kertas Karton - Iga Rahma Kristiani; Mohammad Mirza Fauzie; Narto Narto (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Industrial development in Indonesia increased rapidly. However, some industrial wastes still become problem that need to be solved, such as sengon wood sawdust, cassava peels and HVS used paper. Those wastes contain cellulose that can be utilized for paper board production. Cellulose content of sengon sawdust, cassava peels, and HVS used paper are 67,94 %, 15,20 %, and 58,30 %, respectively. The purpose of this study was to determine the influence of ratio variation among HVS used paper, sengon (Paraserianthes falcataria) sawdust, and cassava(Manihot utilissima) peels on the tensile strength of the papers produced. The type of this research was experiment with post-test only with control group design. The tensile strength measurement were repeated nine times and obtained values for variation ratio 1:0:0 was 0,3785 N/mm, 1:1:2 was 0,7598 N/mm, 1:2:1) was 0,7614 N/mm, and 2:1:1) was 1,0016 N/mm. Statistical test result from one way anova test gained a p-value less than 0,001; meaning that thosetensile strength differences are significant. To conclude, the ratio of HVS used paper, sengon sawdust and cassava peels which yields highest paper tensile strength is 2:1:1.